STRATEGI PENGEMBANGAN WILAYAH-WILAYAH MENJADI PUSAT PERTUMBUHAN BERDASARKAN SEKTOR BASIS DI KABUPATEN MIMIKA - Royandi Gunawan Sihombing; Tharsisius Pabendon (JURNAL KRITIS (Kebijakan, Riset, dan Inovasi), 2020)
This study aims to identify the economic sectors that are the basis sectors for the economy of the sub-regions, and identify the maximum sub-regions in Mimika Regency to be established as the center of economic growth capable of moving the surrounding area, then formulating a regional development strategy in the future. . This research uses quantitative descriptive methods and qualitative descriptive methods. Data collection techniques through surveys and observations, questionnaires and interviews, and documentation of documents as a source of information. The data analysis technique used is to examine the completeness and correctness of the data, analyze the economic sectors of the sub-regional bases, develop strategies for developing regions into growth centers based on the sector basis, and interpret the results of the analysis. From the research results, the district of Mimika Baru has the opportunity to continue to be developed as a center for growth and service. The step that must be done is to implement a strategy to take advantage of opportunities to overcome weaknesses